An investigation in the concept of producing textured cutting tools by using a plasma focus machine - Teh, Thiam Oun; Arwinder, Singh*; Ooi, Jia Yuan; Goh, Eng Hoe; Saw, Sor Heoh; Lee, Sing (AIP Publishing, 2021)
In this paper, the concept of producing a textured tool with a plasma focus machine is investigated for hardness and built-up-edge results. A textured cutting tool is required to have two important characteristics: texture and hardness. The purpose of the texture is to provide a suitable tool surface for a film of solid lubricant to anchor itself. This has the advantage of reducing the possibility of a built-up-edge from occurring in the dry machining of aluminum raw materials. An enhanced hardness provides greater resistance to tool wear. The plasma focus machine is able to deliver both texture and hardness in a single operation, thus making this process a novel approach to toolmaking.